Isolated superficial vein thrombosis in multiple thrombotic defects - Siniscalchi, Carmine; Rocci, Anna (Acta Biomedica Atenei Parmensis, 2019)
Superficial Vein Thrombosis (SVT) is generally a benign, self-limited disorder; however, when larger veins are involved, propagation into deep vein system can occur. Thrombophilic disorders denote several risk factors that predispose individuals to develop venous thromboembolism. It includes inherited thrombophilia, acquired thrombophilia and hyperhomocysteinemia. For thrombophilic patients who develop SVT, the current guidelines don’t clarify for how long time anticoagulation therapy must be performed. We describe a case of SVT in a patient with multiple thrombotic defects, for which we starting Fondaparinux 2.5 mg/die and stopped it when the SVT was solved. During the follow-up period (eighteen months) no Deep Vein Thrombosis or Superficial Vein Thrombosis were detected. Clinical surveillance seems to have been the best strategy for this patient. We believe that this single case report emphasizes the needed of prospective studies to verify the risk of thromboembolic recurrence in thrombophilic patients with SVT. (www.actabiomedica.it)